Environmental DNA: The First Snapshot of the Vertebrate Biodiversity in Three Sicilian Lakes - Mauro, Manuela; Lo Valvo, Mario; Vazzana, Mirella; Radovic, Slobodanka; Vizzini, Aiti; Badalamenti, Rosario; Hornsby, Lucie Branwen; Arizza, Vincenzo (Animals (Basel), 2023)
Freshwater ecosystems play a key role in global diversity and are subject to a series of anthropic impacts, often leading to biodiversity loss. The organisms inhabiting these sites continuously release DNA into the environment through cells, excrement, gametes and/or decomposing matter; thus, evaluation of this eDNA could revolutionize the monitoring of biodiversity. In this study, environmental DNA metabarcoding was used for the first time in three Sicilian lakes: Lake Poma, Piana degli Albanesi Lake and Lake Scanzano. Results obtained provide the first snapshot of vertebrate biodiversity in these three lakes, where little is known, to provide valuable information useful for creating a baseline of knowledge regarding the biodiversity in these three lakes. Another important result was the detection of marine species, most likely due to some kind of anthropogenic contamination. Environmental DNA is a useful tool to evaluate both biodiversity and the ecological status of the environment; it has the potential to complement traditional methods, and the use of both approaches may offer a more comprehensive understanding of the ecosystem.